Effect of LGI1 antibody-positive IgG on hippocampal neuron survival: a preliminary study. Issue 11 (1st August 2018) - Ayşit-Altuncu, Neşe; Ulusoy, Canan; Öztürk, Gürkan; Tüzün, Erdem
Abstract : Anti-leucine-rich glioma inactivated 1 (anti-LGI1) encephalitis is one of the most frequently encountered forms of autoimmune encephalitis. Many patients with anti-LGI1 encephalitis develop permanent hippocampal neuron loss and chronic neuropsychiatric symptoms, suggesting that LGI antibodies (Ab) might have a neurotoxic action. To investigate this hypothesis, purified serum IgG of three patients with anti-LGI1 encephalitis and six healthy controls were incubated with cultured primary hippocampal neurons obtained from newborn mice. Nontreated cells were used as controls. The viability of IgG-treated neurons was evaluated by propidium iodide staining. Apoptotic mechanisms were assessed by JC-1 assay and mRNA expression level measurement of apoptosis-related genes using real-time PCR. The effect of IgG treatment on calcium influx was analyzed by fluo-4 calcium imaging. LGI1-Ab+ IgG increased the number of propidium iodide positive neurons, reduced mitochondrial membrane potentials, upregulated caspase-3 and Bax mRNA expression levels and downregulated Bcl-2 mRNA expression levels of neurons. LGI1-Ab+ IgG-treated neurons showed lower calcium staining than healthy controls IgG-treated and non-IgG-treated neurons. Our results indicate a neurotoxic role of LGI1-Ab. This neurotoxicity is likely mediated through induction of apoptosis and reduction of calcium currents.